The Implementation Of Recollection Smart Teaching Learning Method Can Increase Learning Mathematics Result Of The Eleventh Grade Students Of IPS1 At SMA Negeri 4 Parepare - Arifuddin, Arifuddin (Study Program of Mathematics Education University of Muhammadiyah Malang, 2018)
This research was a classroom action research including planning,implementation, observation, and reflection phase which were implementedin SMA Negeri 4 Parepare which aimed to improve mathematics learningresult through the implementation of learning method of smart teachingrecollection utilizing students‘ unconsciousness in learning process. Subjectsin this study were students class XI IPS1 SMA Negeri 4 Parepare 2016/2017academic year which amounted to 26 students. The research was conductedin 2 cycles, each of cycle was conducted in 4 meetings and carried out thefinal test of it.The data were collected by using observation and learningresult test. The data collected were analyzed by using descriptive statistic.The result of the research showed that the result of mathematics learning ofstudents class XI IPS1 of SMA Negeri 4 Parepare increased from cycle I tocycle II through the implementation of learning method of smart teachingrecollection. This could be seen from (a) the learning results in cycle I, thenumber of students who completed were only 9 students with an averagescore of 64.31 and in cycle II increased to 23 students with an average scoreof 78.27. (b) the increasing percentage of students‘ mathematics learningachievement was 34.6% in the first cycle increased to 88.5% in cycle II. (c)the average increase in the learning activities of the students from cycle I tocycle II. From the results of this research could be concluded that there wasan improvement of students‘ mathematics learning results of class XI IPS1at SMA Negeri 4 Parepare by implementing the teaching method ofrecollection smart teaching.